Treatment Duration and Drug Regimen Correlation with Side Effects Incidence in Drug-Resistant Tuberculosis (DR-TB) Patients at Pulmonary Hospital - Indriani, Lusi; Renitia, Gita Iftitah; Setiani, Lusi Agus (Fakultas Farmasi Universitas Andalas, 2023)
The bacteria Mycobacterium tuberculosis causes Drug-Resistant Tuberculosis (DR-TB). Excessive use of drugs canresult in drug resistance with various side effects. This study aimed to analyze the correlation between the treatment duration and drug regimen with the side effects incidence in DR-TB Patients at Pulmonary Hospital Dr. M. Goenawan Partoidigdo (RSPG) Bogor. This is an observational study with a cross-sectional design. Subjects were selected with purposive sampling methods based on inclusion and exclusion criteria. The research showed that DR-TB patients were mostly male (50.2%) with productive age (46.1%). The most common DR-TB treatment experienced by patients in the advanced phase, generally for 9-24 months (75.3%), and the type of drug side effect most experienced was gastrointestinal disorders, that is nausea (55.1%). The use of standard conventional drug regimens mostly in Z, E, Eto, Km, Lfx, Cs (Pyrazinamide, Ethambutol, Ethionamide, Kanamycin, Levofloxacin, Cycloserine) of 51.4%. The chi-square analysis showed no significant correlation between the treatment duration and the incidence of side effects. At the same time, there was a meaningful correlation between the drug regimen (short-term, long-term, and conventional standard regimen) and the side effects incidence. The suspected drugs causing gastrointestinal side effects were pyrazinamide, ethambutol, ethionamide, and levofloxacin. The side effects of arthritic arthralgia were suspected to be caused by pyrazinamide, ethionamide, and levofloxacin.